2020
DOI: 10.1049/iet-ipr.2018.5942
|View full text |Cite
|
Sign up to set email alerts
|

Symbol positions‐based Slepian–Wolf coding with application to distributed video coding

Abstract: In this study, the authors will show that coding the positions of the symbols, instead of their values, can be a good way to implement efficient Slepian–Wolf (SW) coding and can reduce the complexity of both the encoder and the decoder. The authors will also propose a practical distributed video coding (DVC) system that exploits this idea. This system will use binary maps to indicate the positions of the most probable symbols, instead of separating them into bitplanes. Simulations show that this position‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…4.2, we will present the RD performance results of DVCDL and compare them to those of to the DVC system of Ref. 7, the DISCOVER codec, 17 and H.264/AVC 18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4.2, we will present the RD performance results of DVCDL and compare them to those of to the DVC system of Ref. 7, the DISCOVER codec, 17 and H.264/AVC 18 …”
Section: Resultsmentioning
confidence: 99%
“…The closest SI will have fewer errors to correct (low rate) and will help to reconstruct the best possible quality. For this, many techniques have been proposed to predict a good SI, 19 , 20 but also for improving rate control, 21 channel modeling, 22 better SW coding, 7 quantization, 8 or a better reconstruction of the missing information 9 . Improving SI is the most important way to improve the RD performance because this means finding Y that has the smallest H(X/Y).…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further improve the performance of DVC, researchers have proposed various schemes. A new technique to realize Slepian–Wolf coding was presented in [ 8 ], and it is used for DVC. The authors showed that coding the positions of the symbols, instead of their values, can be a good way to implement efficient Slepian–Wolf coding and can reduce the complexity of both the encoder and the decoder.…”
Section: Introductionmentioning
confidence: 99%